The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m304010200
|View full text |Cite
|
Sign up to set email alerts
|

Hyperproliferation and p53 Status of Lens Epithelial Cells Derived from αB-crystallin Knockout Mice

Abstract: ␣B-Crystallin, a major protein of lens fiber cells, is a stress-induced chaperone expressed at low levels in the lens epithelium and numerous other tissues, and its expression is enhanced in certain pathological conditions. However, the function of ␣B in these tissues is not known. Lenses of ␣B؊/؊ mice develop degeneration of specific skeletal muscles but do not develop cataracts. Recent work in our laboratory indicates that primary cultures of ␣B؊/؊ lens epithelial cells demonstrate genomic instability and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 65 publications
2
36
0
Order By: Relevance
“…Until recently very little information was available on the effect of expression of ␣A-and ␣B-crystallin on the microtubule cytoskeleton. Our previous work with ␣A-/-and ␣B-/-lens epithelial cells had demonstrated that ␣A-and ␣B-crystallin have important but distinct effects on the integrity of the mitotic spindle microtubules (18,20). A loss of microtubules was observed in some of the anaphase spindles of ␣A-/-and ␣B-/-cells between the separating chromosomes (18,20).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Until recently very little information was available on the effect of expression of ␣A-and ␣B-crystallin on the microtubule cytoskeleton. Our previous work with ␣A-/-and ␣B-/-lens epithelial cells had demonstrated that ␣A-and ␣B-crystallin have important but distinct effects on the integrity of the mitotic spindle microtubules (18,20). A loss of microtubules was observed in some of the anaphase spindles of ␣A-/-and ␣B-/-cells between the separating chromosomes (18,20).…”
Section: Discussionmentioning
confidence: 95%
“…Our previous work with ␣A-/-and ␣B-/-lens epithelial cells had demonstrated that ␣A-and ␣B-crystallin have important but distinct effects on the integrity of the mitotic spindle microtubules (18,20). A loss of microtubules was observed in some of the anaphase spindles of ␣A-/-and ␣B-/-cells between the separating chromosomes (18,20). The current work suggests that this phenotype may be the result of poor microtubule nucleation and/or destabilization of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…30 Cells were also colabeled with a ␤-tubulin antibody and an Alexa-568 -labeled secondary antibody to allow visualization of the microtubule cytoskeleton. 31 Cells were examined by confocal microscopy. 31 Four random microscopic fields were examined under each condition.…”
Section: Irradiation Of Cell Cultures For Confocal Microscopymentioning
confidence: 99%
“…Moreover, mutation or lack of the aA gene induces cataract in mice and humans [13], while mutation or lack of the aB gene causes a desmin-related myopa-* Corresponding author. thy [14] or hyperproliferation and genomic instability, respectively [15,16]. A common feature of sHsps is a conserved C-terminal region of about 90 amino acids called the 'a-crystallin domain,' responsible for their molecular chaperone action.…”
mentioning
confidence: 99%